Pengaruh Thin Capitalization dan Capital Intesity dengan Kepemilikan Institusional sebagai Variabel Moderating Terhadap Tax Avoidance - Gracea Olivia Lucky; Murtanto murtanto (Publikasi Indonesia, 2022)
This aims to examine the effect of Thin Capitalization and Capital Intensity on Tax Avoidance and to examine Institutional Ownership in moderating the effect of Thin Capitalization and Capital Intensity on Tax Avoidance in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2020 period. This study uses a sample of 19 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2016-2020 period with the sampling technique using the purposive sampling method and the research data using secondary data. Data analysis used moderated regression analysis with STATA software. The results of this study indicate that Thin Capitalization has a negative effect on Tax Avoidance, while Capital Intensity has no effect on Tax Avoidance and Institutional Ownership can moderate Thin Capitalization and Capital Intensity on Tax Avoidance.